Forage production in a natural grassland with limestone and phosphorus dosages - Prestes, Nelson Eduardo; Amarante, Cassandro Vidal Talamini do; Pinto, Cassiano Eduardo; Prestes, Gabriel; Zanini, Guilherme Doneda; Medeiros-Neto, Cauby; Sbrissia, André Fischer (Semina: Ciências Agrárias, 2016)
The objective of this study was to assess forage production in a natural grassland by applying different doses of limestone and phosphorus, and the influence of these applications on soil profile. The treatments consisted of the application of limestone doses of 0.0, 7.2, and 14.4 t ha-1 and phosphorus doses of 0,35, 70, and 140 kg of P2O5 ha-1 on the soil surface. The experiment was conducted in a randomized complete block design with split-plots and three replications. The limestone doses were distributed in the main plot and applied only at the beginning of the experiment, whereas the phosphorus doses were distributed in the subplots with subsequent annual maintenance applications. Was used a ruler (cm) for monitoring the growth of pastures and, when grasses reached an average height of 20 cm, forage samples were collected in each subplot and botanical and morphological components were separated and dried until a constant weight was achieved. In the third and fourth assessment years, soil samples were collected in the 0-5, 5-10, 10-15, and 15-20-cm layers to evaluate the influence of treatments on the chemical properties of the soil. The variables analyzed were related to the production of several components, including fodder, native grasses, leguminous plants, unwanted plants, and dead material, in addition to soil properties such as pH, exchangeable aluminum concentration, and base saturation. There was no interaction between the limestone and phosphorus treatments. The effect of limestone doses on forage production was assessed in the third year, and, in the following year, the intermediate dose of limestone (7.2 t ha-1) produced the highest yield (2,316.1 kg of dry matter [DM] of forage ha-1). The increase in phosphorus doses increased forage production in the second year, and reached yields of up to 2,232 Kg DM ha-1 in the fourth year. In summary, the production of natural pastures was enhanced by the application of 25% of the recommended dose of limestone (7.2 t ha-1), and by the application of 50% of the recommended dose of phosphorus (70 kg P2O5 ha-1). The increase in limestone doses directly affected the chemical properties of the soil by decreasing acidity and exchangeable aluminum, and increasing base saturation, even in deeper layers (0-20 cm). The increase in phosphorus doses did not increase the mobility of this nutrient in the deeper layers of the soil (10-20 cm), and the effects were restricted to a depth of up to 10 cm.